Biology of the Hicatee: A Critically Endangered River Turtle of Belize - Venetia Briggs-Gonzalez; Nathan Schwartz; Rebecca G. Harvey; Frank J. Mazzotti (EDIS, 2015)
The hicatee (Dermatemys mawii) is a Central American river turtle and one of the 25 most endangered turtle species in the world. Over-hunting for meat, eggs, and shells is driving the turtles toward extinction. This 3-page fact sheet about the hicatee includes its natural history, reproductive habits, and ecology and describes the international conservation efforts to save the fascinating but fast-disappearing turtle. Written by Venetia Briggs-Gonzalez, Nathan Schwartz, Rebecca G. Harvey, and Frank J. Mazzotti and published in November 2015 by the Wildlife Ecology and Conservation Department.